2019
DOI: 10.32598/hdq.4.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Mass Casualty Response to Mine Explosion: A Case Report in Iran

Abstract: AM local time, an explosion occurred in the Zemestan-Yurt coal mine in Azadshahr City of Golestan Province, northern Iran, which resulted in mass casualty incident. Materials and Methods: In total, more than 126 miners were affected. Of them, 43 miners were killed, 73 other workers who helped their coworkers were also injured and taken to the hospital, and 10 injured people received on-site prehospital medical care. Many defects in the response phase were identified in the scene management and the triage. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The reason for this inconsistency could be attributed to the lack of a joint inter-organizational response plan and effective training programs. Similarly, Mohajer-Vatan in a study addressed this issue by evaluating the response of the pre-hospital system to the Zemestan-Yurt Mine explosion [9]. In the mentioned study, the main problems were reported as the lack of organizational coordination and suitable equipment, being consistent with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…The reason for this inconsistency could be attributed to the lack of a joint inter-organizational response plan and effective training programs. Similarly, Mohajer-Vatan in a study addressed this issue by evaluating the response of the pre-hospital system to the Zemestan-Yurt Mine explosion [9]. In the mentioned study, the main problems were reported as the lack of organizational coordination and suitable equipment, being consistent with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…However, despite having quick access to the accident scene, some of the relief efforts lacked integrity, rendering them ineffective. Interventions involved locating the collection zone, triage area, and injured persons in the waiting area for loading, which are crucial tasks for the response teams according to other studies [30]. Triage is one of the most significant pre-hospital emergency challenges in accidents, where a lack of resources requires prioritization of patients.…”
Section: Field Performancementioning
confidence: 99%